Conscientiousness and perceived ethicality: Examining why hierarchy of authority diminishes this positive relationship - Luksyte, A.; Carpini, J.A.; Parker, Sharon; Griffin, Mark (2024)
Human resource (HR) managers hire conscientious employees because they are both productive and are viewed as upholding high ethical standards due to their propensity to engage in voice. Organizations may strive to create a work context conducive to all employees acting ethically, not just conscientious ones, by centralizing decision-making authority and promoting formalization through a higher hierarchy of authority. Yet, we propose that from the social information processing perspective, in higher hierarchy of authority contexts, peers may view their highly conscientious colleagues as less ethical. We hypothesize these effects through the lens of trait activation theory, according to which in a higher hierarchy of authority context, others are less likely to notice the voice behaviors of conscientious employees. Problematically, when others fail to notice conscientious employees' voice, they may perceive these workers as being less ethical. We tested our hypothesized moderated mediation model in a matched sample of employees (N = 820), their supervisors (N = 445), and peers (N = 529). As predicted, hierarchy of authority moderated the positive relationship between conscientiousness and voice, which in turn explained others' perceptions of their ethicality. Conscientiousness was positively related to peer assessments of ethicality via promotive (not prohibitive) voice when hierarchy of authority was lower (but not higher), partially supporting our hypotheses. These results suggest HR practitioners should be cognizant of the differential evaluations of highly conscientious employees in contexts with different levels of hierarchy of authority, and continuing challenges associated with balancing flexibility and formalization.